Public perceptions of pharmacist expanded scope of practice services in Nova Scotia. (September 2015) - Bishop, Andrea C.; Boyle, Todd A.; Morrison, Bobbi; Barker, James R.; Zwicker, Bev; Mahaffey, Tom; Murphy, Andrea
Background: Community pharmacists have been transitioning from traditional dispensing roles toward a much broader scope of practice. The objective of this research was to explore public perceptions of expanded scope of practice (ESOP) services as they relate to pharmacy and pharmacist characteristics. Methods: The Survey on New Services Offered by Nova Scotia Pharmacists was developed and deployed using in-pharmacy intercept surveys and online public surveys in Nova Scotia. The survey focused on 4 key ESOP elements/services: 1) prescribing for minor ailments (ambulatory conditions), 2) injections and vaccinations, 3) prescription renewals and 4) medication reviews. Data were analyzed using comparisons between groups (multivariate analysis of variance) and principal component analysis. Results: A total of 385 surveys were obtained from the public regarding their perceptions and use of ESOP services (online n = 237, in-pharmacy intercept n = 148). A number of significant differences were found on the basis of respondent sex, age and the location of survey deployment. Discussion: Overall, public perceptions of pharmacists' knowledge and skills in providing ESOP services are positive. A pharmacist's ability to communicate, protect confidentiality and provide quality information regarding medications is important to the public. Conclusion: Respondents who already have a good relationship with their pharmacist are more likely to see value in ESOP services. Future public education strategies should focus on factors positively affecting the public's perceptions of ESOP services and should encourage public use of these services through intentional patient education of the benefits of ESOP services and strengthening of the patient-provider relationship.